Hubungan Antara Perilaku Keselamatan Dan Kesehatan Kerja (K3) Dengan Kejadian Kecelakaan Kerja Pada Pekerja Di PT Aneka Adhilogam Karya, Ceper, Klaten - Pertiwi, Pujiani, Tarwaka, PGDip Sc, M.Erg, Sri Darnoto, SKM, M.PH (2016)
Behavior-based safety is a part of the process of controlling risks to unsafe behavior as the cause of the accident. Objective of this research is to know relationship between behavior of occupational safety and health with work accident on workers at PT Aneka Adhilogam Karya, Ceper, Klaten. Method of this research use analytic survey design with cross sectional approach. Population in this research is all workers at induction, stamping, casting, machining, and finishing section as much as 84 respondents. Simple random sampling used for 46 respondents. Statistical tests using pearson product moment. The results showed that 45.7% of workers behave 67.4% of insecurity and shows high work accident occurrence frequency. The results of statistical tests showed no significant relationship (p value 0.201 ≥ 0.05) between the behavior of occupational safety and health with work accident on workers at PT Aneka Adhilogam Karya, Ceper, Klaten. Based on this research the safety culture can prevent accidents in this company.